(3bGYOI LdjdI aj GdJhSd hGdhSjdI (B/s - (3Hf JjejI, CMeO Hf YHO GdMdje Hf YHO GdSdGes 661-728 (3g`(B.s; (3GdeONdj, QHjY Hf gGOjs ((3HjQhJ (B:s (3ecJHI GdaQbGf,s, 2001)
(3gPG GdcJGH jbOe GdJhSd GdeTQhY hZjQ GdeTQhY Hcde LjO heJjf hCOdI hGajI(B.s
Keywords: (3GdTaGYIs; (3GdJhSds; (3GdhSjdIs; (3GdSeYjGJs